One Step Carbonization/Activation Process for Carbonaceous Material Preparation from Pecan Shells for Tartrazine Removal and Regeneration after Saturation. Issue 10 (December 2015) - Torres-Pérez, J.; Soria-Serna, L.A.; Solache-Ríos, M.; McKay, G.
The removal of tartrazine dye (A5) onto activated carbon produced from pecan nut shells ( Carya illinoinensis ) obtained under specific conditions and one step simultaneous carbonization/activation process was carried out in this work. First order, pseudo-second order and Elovich adsorption kinetic models were applied for the kinetic studies. The experimental equilibrium data were analysed using the isotherms of Langmuir, Freundlich and Temkin. Batch adsorption studies were performed for the removal of tartrazine azoic dye from aqueous solutions by two materials obtained at 600 °C (NAC-600) and 857 °C (NAC-857) and another two materials prepared at the same temperatures but simultaneously activated with steam (NAC-600-H2 O and NAC-857-H2 O). The zero point charge was between pH values of 9 to 11 and the maximum adsorption occurred when activated carbons were steam activated and were 4.47 and 13.66 mg g −1 for NAC-600-H2 O and NAC-857-H2 O respectively. The results clearly showed that the adsorption of A5 onto carbonaceous materials from nut shells (NAC) best fit to the pseudo second- order model, and the rate constants were in the range from 489.3 to 509.4 g mg −1 h −1 . Maximum uptake capacity of tartrazine was comparable to values encountered in the literature for other carbonaceous materials. The results show that under specific activation conditions, Mexican pecan nut shells, as agricultural residues, present high potential as a raw material to produce alternative adsorbent materials for dyes removal from aqueous solutions.